ESTRUS INDUCTION AND FERTILITY RESPONSE IN POSTPARTUM ANOESTRUS SURTI BUFFALOES TREATED WITH NORGESTOMET EAR IMPLANTS ALONE AND IN COMBINATION WITH PMSG - PARMAR, S C; KHASATIYA, C T; PATEL, M D; CHAUDHARY, J K; PATEL, R V (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on eighteen postpartum anoestrus (> 45 days postpartum) Surti buffaloes,divided into three equal groups (6 in each) to evaluate the efficacy of Norgestomet ear implant/Crester alone(Gr-I) and in combination with PMSG (Gr-11). The buffaloes in Group-I and Group-II were implanted with Crestarear implant for 9 days with 2 ml i/m injection of Crestar solution (estradiol valerate) on the day of implantinsertion. In Group-II, additionally 500 IU PMSG was given i/m on the day of implant removal. The buffaloesin Group-Ill served as untreated anoestrus controls and were given 5 ml normal saline i/m as a placebotreatment on days 0 and 9. The estrus was induced in all buffaloes in Gr-I and II with mean estrus inductionintervals of 2.56 ± 0.34 and 2.40 ± 0.29 days, respectively. These intervals were significantly (P
Keywords: Buffaloes; Postpartum anoestrus; Norgestomet ear implant; PMSG; Estrus; Fertility